Microcystic Stromal Tumor with Predominant Bizarre Nuclei of Ovary in a Pregnant Woman. (7th December 2022) - Pongsuvareeyakul, Tip; Kingnate, Chalita; Sukpan, Kornkanok; Khunamornpong, Surapan
Abstract : Microcystic stromal tumor (MST) is a rare type of pure stromal tumor in the category of ovarian sex cord-stromal tumors. It is characterized by a distinctive microcystic appearance with bland tumor cells. Although the pathological diagnosis can be straightforward based on the typical histomorphology in most MSTs, the cases with morphologic variation can pose a diagnostic challenge due to unfamiliarity of pathologists with the histologic spectrum of MST and its negativity for inhibin and calretinin, the commonly used sex cord-stromal markers. The coexistence between MST and mucinous epithelial tumor is extremely rare. We present the first case, to our knowledge, of ovarian MST with predominant bizarre nuclei coexisting with mucinous cystadenoma in a pregnant woman. The histomorphology in this case presents a diagnostic challenge and raises differential diagnosis for a wide variety of ovarian malignant neoplasms including nonneoplastic lesions.